2020
DOI: 10.21203/rs.3.rs-40387/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do Population Density, Socio-Economic Ranking and Gini Index of Cities Influence Infection Rates from Coronavirus? Israel as a case Study

Abstract: Abstract A prominent characteristic of the COVID-19 pandemic is the marked geographic variation in COVID-19 prevalence. The objective of the current study is assess the influence of population density and socio-economic measures (socio-economic ranking and the Gini index) across cities on coronavirus infection rates. Israel provides an interesting case study based on the highly non-uniform distribution of urban populations, the existence of one of the most densely popul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
2
4
1
Order By: Relevance
“…The net population density was positively and significantly associated with the virus infection. This is consistent with the results of previous studies that found a strong association between population density and infectious disease outbreak [ 8 , 27 ]. Interestingly, net employment density was not statistically significant in the model.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The net population density was positively and significantly associated with the virus infection. This is consistent with the results of previous studies that found a strong association between population density and infectious disease outbreak [ 8 , 27 ]. Interestingly, net employment density was not statistically significant in the model.…”
Section: Discussionsupporting
confidence: 93%
“…Hamidi et al [ 32 ] considered the vulnerable population, including the elderly, and the level of medical services and facilities, in addition to density, as the main factors affecting the spread of COVID-19 and mortality in the United States. Arbel et al [ 27 ] and Ehlert [ 28 ] reported that socioeconomic factors other than density are closely related to the COVID-19 fatality rate. Identifying the effect of social distancing on trip reduction in U.S. metropolitan areas, Hamidi & Zandiatashbar [ 59 ] employed demographic attributes, park accessibility, as well as density.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated coefficients of population density are small and statistically insignificant, suggesting no meaningful link between population density and confirmed cases of Covid-19 at the global level. However, this result does not rule out the possibility of a positive association between population density and virus infection at the individual country or, for that matter, at a city level, as reported by Arbel et al (2020) for Israeli cities, among other studies.…”
Section: Resultscontrasting
confidence: 57%
“…For Brazil, there is evidence of a positive and significant correlation between income inequality and COVID-19 mortality (Demenech et al, 2020;Martines et al, 2021). Studies conducted in Germany, Israel and Spain have shown that infection rates in these countries have varied based on income inequality, with socioeconomically disadvantaged populations being more likely to be infected (AQuAS, 2020;Arbel et al, 2020;Wachtler et al, 2020). A comparative study of the 10 countries worldwide that have been the most affected by the pandemic used a multidimensional index, including income inequality, to show that the worse off a country is, the greater the impact of COVID-19 has been (Ruiz Estrada, 2020).…”
Section: Introductionmentioning
confidence: 99%